2007
DOI: 10.1002/chin.200725200
|View full text |Cite
|
Sign up to set email alerts
|

A New Prenylated Isoflavone from Tephrosia tinctoria.

Abstract: A New Prenylated Isoflavone from Tephrosia tinctoria. -The title compound (I) is isolated from the roots of Tephrosia tinctoria and represents the rare occurrence of an O-geranylated isoflavone from a natural source. -(REDDY, B. A. K.; KHALIVULLA, S. I.; GUNASEKAR*, D.; Indian J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Forty-two isoflavones, 94 – 13 5 , have been isolated and identified from this genus [5,22,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91]. Among them, 111 – 125 were identified as rotenoids [74,75,76,77,78,79,80,81,82], 94 and 126 – 13 5 were identified as coumestan derivatives [22,83,84,85,86,87,88,89,90,91].…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Forty-two isoflavones, 94 – 13 5 , have been isolated and identified from this genus [5,22,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91]. Among them, 111 – 125 were identified as rotenoids [74,75,76,77,78,79,80,81,82], 94 and 126 – 13 5 were identified as coumestan derivatives [22,83,84,85,86,87,88,89,90,91].…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…73 Screening of the purified compounds indicated that the neuroprotective activity of the crude extract was not associated with 21 (but see 127). An active MeOH extract of the leaves of this species afforded brandisianins A-E (28-32), together with a pterocarpan, brandisianin F (see 90). 74 These are presumably derived from 6,8-diprenylbiochanin A, which was a major component of the same extract.…”
Section: Prenylated Isoflavonesmentioning
confidence: 99%
“…In bioassays, 2 0 -prenylorobol (45) showed significant antileishmanial and trypanocidal activity, but low selectivity (3-fold) for parasites compared to mammalian Vero cells. 90 The structure 6,8,3 0 ,4 0 -tetrahydroxy-2 0 -methoxy-7-methyl-6 0 -(1,1-dimethylprop-2-enyl)isoflavone assigned to a constituent of Lespedeza cuneata (Dum. Structural elucidation was based on the use of capillary scale NMR (see Section 1.1.2).…”
Section: Prenylated Isoflavonesmentioning
confidence: 99%
See 1 more Smart Citation
“…is an erect undershrub found widely in Talakona forest, Andhra Pradesh, South India [7]. Earlier investigation on the roots of this species [8] has resulted in the isolation of 7-O-geranylbiochanin A, a new O-geranylated isoflavone. As part of our ongoing studies on this species, we investigated the stems of T. tinctoria and report here the isolation and characterization of a new di-O-prenylated isoflavone, 5,7-di-O-prenylbiochanin A (1) together with two known flavanones, 7-Omethylglabranin (2) [9] and tephrowatsin C (3) [10], and a known pterocarpene, flemichapparin B (4) [11,12].…”
Section: Introductionmentioning
confidence: 99%